FEATURES OF ADMINISTRATIVE-TERRITORIAL POSITION OF RUSSIA IN THE EARLY XIX CENTURY (AS EXEMPLIFIED BY SIBERIA) - D. N. Gergilev; N. S. Dureeva (Вестник Кемеровского государственного университета, 2017)
The article features the formation and development of state power in Siberia in the early XIX century. The authors conducted a comparative analysis of management tools formed as a result of the provincial reforms of Catherine II. In addition, the authors analyze the contradictory tendencies characteristic of the first phase of the reign of Alexander I. The special role of I. O. Selifontov and his project of administrative reform in the formation of management policies in Siberia is reported. It is shown that the result of the audit conducted by Selifontov was the formation in 1803 of a united Siberian General-governorship with the centre in Irkutsk and that, together with the new position, the new Governor-General received special instructions, which greatly expanded his powers. It is shown that the purpose of Selifontov’s administrative reforms was the expansion of the influence of the GovernorGeneral's authority on the financial and economic part of the local management. The article reveals the inconsistency of Selifontov’s successor B. Pestel and his administration. It is proved that Siberia got involved in the course of world history precisely because it joined the Russian State.